Determination of fatty acid profiles and bioactive properties of body wall and viscera of Holothuria atra collected from Lombok Island, Indonesia. Issue 1 (1st December 2022) - Putra, Y; Soffa, F B; Firdaus, M; Pangestuti, R; Siahaan, E A
Abstract: Holothuria atra is one of the most abundant sea cucumbers found in Indonesia and known to possess various bioactivities. In this study we determined the antioxidant, antibacterial activity, and fatty acids of body wall and viscera of H. atra . Samples were collected from North Lombok. Fatty acid profile of fresh H. atra was examined by gas chromatographic quantification. Four different solvents (ethanol, methanol, ethanol mixed with water, and ethanol mixed with acetone) were used to extract the phenolic content of the viscera and body wall of H. atra . It is found that the fatty acids eicosapentanoic acid (EPA) and docosahexanoic acid (DHA) amount of body wall were higher than viscera of H. atra ; The results showed H. atra contained 8.56% EPA and 1.6% DHA in the body wall followed by 0.1% EPA and o.37 DHA in the viscera. The extract of body wall of H. atra using ethanol acetone mixture has low antioxidant activity with value of 16.05±0.78mg/mL and the strong antioxidant activity was found in ethanolic extract of H. atra viscera (2.77±0.88 mg/mL). Antibacterial activity of body wall and viscera of H. atra against gram negative and positive bacteria including Pseudomonas aeruginosa, Bacillus subtilis, Escherichia coli, Staphylococcus aureus were conducted by using agar diffusion method.